Factors influencing mathematics teachers’ pedagogical content knowledge: A systematic review - SAKARIA, DARMARAJ; MAAT, SITI MISTIMA; MOHD. MATORE, MOHD EFFENDI EWAN (Pegem Journal of Education and Instruction, 2023)
Pedagogical content knowledge pertains to a mix of mathematics subject content and pedagogy knowledge that leads to an understanding of how mathematics subjects, issues, and problems are arranged and utilized in teaching. Mathematics teachers play the most pivotal role in reflecting students’ abilities and interests, and also provide conceptual understanding by having high PCK. However, research that comprehensively analyses the available literature relating to factors that could affect mathematics teachers’ PCK are still lacking. There is a compelling demand to strengthen our present mathematics teachers in order to close this gap to boost their competence and raise their PCK level. As a result, the purpose of this research is to investigate the aspects that influence the PCK of the mathematics teachers, with a focus on primary and secondary mathematics teachers. The Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) were utilized to perform the systematic review. The Web of Science (WOS) and Scopus databases were used to access the evaluated publications in this research from January 2018 to January 2022. The findings revealed that mathematics teachers’ PCK are influenced by three types of factors: individual, professional and organizational factors. Professional development and teaching experience are the two factors with the highest frequency and dominance. The outcomes of this research can be employed as a maneuverer for researchers in the field of mathematics education who are embarking on PCK studies. This article also makes recommendations for further research on mathematics teachers’ PCK.